Difficulties and Challenges in Teaching Language to Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article discusses some difficulties and challenges in teaching language to children. Several challenges and the ways of overcoming these difficulties have been given.